British Birds : A Pocket Guide - Hume, Rob; Tipling, David; Harrop, Hugh; Swash, Andy; Still, Rob (Book collections on Project MUSE., 2019)
A carefully designed and lavishly illustrated photographic guideThis innovative and carefully designed photographic guide provides a concise introduction to the identification of the 246 birds most likely to be seen in Great Britain and Ireland. It is the perfect book for anyone wanting to put a name to the birds in their garden, local area or on visits farther afield. Packed with hundreds of stunning photos showing the birds in their many variations, and written and designed by a team of experienced birdwatchers, this is the ideal companion for anyone interested in learning more about the wild birds around us. Covers the 246 birds most likely to be seen, plus another 30 or so scarce but regular migrantsCarefully designed to be user-friendly and accessibleLavishly illustrated with more than 1,000 stunning colour photographsEasy to use and written in plain English.